Argentine ´s representatives and representations in the International Labor Organization on the 1920 ´s - Stagnaro, Andres; Caruso, Laura (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2017)
The article approach the relations between the Argentine and the International Labor Organization (ILO) through the different argentine ´s representatives on the ILO ´s annual conferences during the formative process on the 1920 ´s. The representative ´s reports –in the case of the government ´s representatives those reports were raised to the authorities, in the case of the workers and employers delegates the reports were published in different publications– allowed us to analyze those delegates expectations while they interact with a an organizations with their own objectives. In many cases the ILO was just another stage in the dispute between the state, the workers and the employers, in others we will be able to see the uniformity of criteria in some topics, such as the spot of argentine ´s labor legislation. At the same time, Argentine ´s participation on the ILO ´s conferences demands the adequacy of the relations system between the State and the workers unions. In the absence of this kind of mechanism the workers representative elections depends on the moment of local labor unrest.